Analyzing e-governance assessment initiatives: an exploratory study - Alarabiat, Ayman (2018)
This paper presents an exploratory study aimed at identifying, exploring, and analyzing current EGOV assessment initiatives. We do so based on data obtained from a desktop research and from a worldwide questionnaire directed to the 193 countries that are part of the list used by the Statistics Division of the United Nations Department of Economic and Social Affairs (UNDESA). The study analyses 12 EGOV assessment initiatives: a) seven of them are international/regional EGOV assessment initiatives performed by the United Nations (UN), European Union (EU), Waseda-IAC, Organisation for Economic Co-operation and Development (OECD), World Bank (WB), WWW Foundation, and Open Knowledge Network (OKN); b) five of them are country level EGOV assessment initiatives performed by Norway, Germany, India, Saudi Arabia, and the United Arab Emirates. Further, the study provides general results obtained from a questionnaire with participation from 18 countries: Afghanistan, Angola, Brazil, Cabo Verde, Denmark, Estonia, Finland, Germany, Ghana, Ireland, Latvia, the Netherlands, Norway, Oman, Pakistan, the Philippines, Portugal, and Slovenia. The findings show that there is no shortage of interest in assessing EGOV initiatives. However, the supply side of EGOV initiatives is the dominant perspective being assessed, particularly by regional and international organizations. While there is an increasing interest in assessing the users’ perspective (demand side) by individual countries, such attempts still seem to be at an early stage. Additionally, the actual use and impact of various EGOV services and activities are rarely well identified and measured. This study represents a stepping stone for developing instruments for assessing EGOV initiatives in future works. For the current stage, the study presents several general suggestions to be considered during the assessment process.